Ecología de Aechmea nidularioides L.B.SM (bromeliaceae) en bosque de varillal alto seco y propuesta de conservación en la Reserva Nacional Allpahuayo Mishana - Cubas Guerra, Rossana (2022)
From october 2016 to september 2017 I registred the abiotics factors the White sand forest where alive Aechmea nidularioides, in the Allpauayo Mishana National Reserve (AMNR), by direct observation. Environmental temperature average for AMNR various between 33.8 to 22°C and undergrowth of the White sand forest it was variable with maximum temperature during the day 33.5 to 29.5 °C and minimum temperature 27 to 22.4°C, while what the relative humidity in the Alpahuayo Mishana National Reserve various 94.33 to 74.67%. Rain precipitation in the AMNR for sector PV Irapay it was 3288.5 mm for sectors Llanchama and Mishana (Nanay river) 2725.8 mm the water. Percentage of sunlight in the White sand forest various 10 to 15 % according height, density of the trees and canopy. Come in the biotics factors, flowering occurs only once between february and august; density was variable (n= 45 plots) with 7 ind/25m2 and with a mainly vegetative mode of reproduction 1, 2 or 3 young, from lateral rhizomes present on the stem of the mother bromeliad; the floristic composition VAS was made up of 56 families with 142 species with predominance of Fabaceae, Aracaceae, Lauraceae and Sapotaceae, the same ones thatproduce the shade necessary for the development of Aechmea nidularioides in the VAS; likewise, phytotelmas from to Aechmea nidularioides are used by Anolis spp., Bolitoglossa altamazonica, Osteocephalus spp.,Ranitomeya reticulata y R. amazonica and spiders. It is concluded that Aechmea nidularioides develops in shaded conditions produced by the vegetation cover of the VAS and that are used by species of invertebrates and vertebrates.